GREETING AND LEAVE TAKING AMONG NATIVE SASAK IN LOMBOK - Atika, Istikhorini (Masyarakat Linguistik Indonesia, 2020)
Greetings and leave-takings are conversational routine used to maintain person?s relationship in society. However, each culture may have different ways of expressing them. In English, the common greetings and leave-takings pattern used are time-free and time-bound greeting expressed by good afternoon, good evening, good night, nice to meet you and so forth. These are not found in Sasak, so they may cause problem for native Sasak speaker to understand another culture greetings and leave takings; conversely for non-native Sasak speaker who intends to learn them as well. The aim of this study is to find out the forms of greeting and leave taking that appear in Sasak. This study uses ethnography design. To collect the data, observation sheet is utilized. Then, using Haliday?s theory of time-free and time-bound greeting, the data is analyzed by comparing and contrasting greeting and leave-taking patterns used in English and Sasak. The result of the study indicates that Sasak types of greeting and leave taking consist of time-free and time-bound greeting. However, these forms are not exactly the same with common English greeting and leave-taking, they tend to be more phatic utterance (speech act which function to show solidarity and empathy). Therefore, the English curriculum linked with greeting and leave-taking material needs to be associated with Sasak greeting and leave-taking forms in order to create students? better understanding.